Meta-analysis of the effect of comprehensive smoke-free legislation on acute coronary events. Issue 19 (23rd August 2010) - Mackay, D F; Irfan, M O; Haw, S; Pell, J P
Abstract : Objective: To assess the evidence for a reduced risk of acute coronary events following comprehensive smoke-free legislation. Methods: Two independent systematic reviews were undertaken using PubMed, Embase and Science Direct with no date restrictions imposed. Meta-analysis was undertaken using a random effects model to obtain a pooled estimate of the relative risk. Linear regression was used to examine possible bias and meta-regression was used to investigate possible causes of heterogeneity. Main outcome measure: Acute coronary events. Results: The 17 eligible studies (10 from North America, 6 from Europe and 1 from Australasia) provided 35 estimates of effect size. Apart from five subgroup analyses, all of the published results suggested a reduction in the incidence of acute coronary events following the introduction of smoke-free legislation. Meta-analysis produced a pooled estimate of the relative risk of 0.90 (95% CI 0.86 to 0.94). There was significant heterogeneity (overall I 2 =95.1%, p<0.001) but there was no evidence of small study bias (p=0.714). On univariate random effects meta-regression analysis, studies with longer data collection following legislation produced greater estimates of risk reduction and remained significant after adjustment for other study characteristics (adjusted coefficient −0.005, 95% CI −0.007 to −0.002, multiplicity adjusted p=0.006). Conclusions: There is now a large body of evidence supporting a reduction in acute coronary events following the implementation of comprehensive smoke-free legislation, with the effect increasing over time from implementation. Countries that have not yet adopted smoke-free legislation should be encouraged to do so.